Cutaneous hypersensitivity induced in dogs and guinea-pigs by extracts of the tick Rhipicephalus sanguineus (Acari: Ixodidae) - Szabó, M. P J; Morelli, J. [UNESP]; Bechara, G. H. [UNESP] (My University, 1995)
The cutaneous hypersensitivity induced by Rhipicephalus sanguineus tick extract in dogs (natural host) and guinea-pigs (laboratory host) was evaluated. The left ear of infested and control (tick-bite naive) dogs and guinea-pigs was injected intradermally with an extract from unfed adult ticks and the right ear with phosphate buffered saline (PBS). Ear thickness variations were then measured after 10 min and 1, 2, 6, 18, 24, 48, 72 and 96 h post-injection. Results were expressed as percentual changes in the ear thickness in relation to pre-inoculation values. The final variation in ear thickness induced by the extract was given by subtracting, in each animal, the right ear percentual increase from that of the left ear. Guinea-pigs were tested at two different times following infestation and with two different doses of extract. Infested guinea-pigs from the three experiments developed an immediate (within the first 2 h post-inoculation) and a strong delayed reaction (24 h) to the extract. Dogs, unlike guinea-pigs, developed only a strong immediate reaction whereby an 80% increase in ear thickness was observed. Control animals, with the exception of one dog, did not develop any significant reaction to the extract. Only mild reactions were induced by PBS in the right ear of all animals. The correlation between the absence of a strong delayed type reaction to tick extract and the lack of resistance of the natural host to R. sanguineus tick is discussed. © 1995 Chapman & Hall.
Keywords: cellular immunity; dog; guinea-pig; Hypersensitivity; intradermal test; Rhipicephalus sanguineus; tick